Beyond anti-VEGF: expanding the therapeutic horizon and biomarker landscape in retinopathy of prematurity - Zhang, Yuxin; Chen, Qian; Lv, Jianli (Frontiers in Pediatrics, 2026)
BackgroundRetinopathy of prematurity (ROP) remains a leading cause of childhood blindness worldwide. While anti-VEGF therapy has revolutionized ROP treatment, concerns regarding systemic absorption, potential neurodevelopmental impacts, and late reactivation have spurred the quest for alternative therapeutic approaches. This mini-review examines emerging therapeutic targets and novel biomarkers that may transform ROP management beyond the anti-VEGF era.MethodsWe conducted a comprehensive literature review of studies published between 2001 and 2025, focusing on novel therapeutic mechanisms, biomarker discovery, and translational research in ROP.ResultsSeveral promising therapeutic targets have emerged, including: (1) IGF-1 supplementation and IGF-1/IGFBP3 complex therapy; (2) Omega-3 polyunsaturated fatty acids, demonstrating anti-inflammatory and anti-angiogenic properties; (3) Antioxidant therapies targeting oxidative stress pathways; (4) HIF-stabilizing agents that promote physiological vascularization; (5) Cell-based therapies using mesenchymal stem cells and (6) Non-selective beta-adrenergic receptor blockers (propranolol), which target the sympathetic drive of pathological neovascularization. Novel biomarkers under investigation and advanced imaging biomarkers using OCT angiography. Combination approaches integrating multiple pathways show particular promise.ConclusionsEmerging therapies targeting multiple pathogenic mechanisms, combined with novel biomarkers for risk stratification and treatment monitoring, show potential for more personalized and effective ROP management. Future research should focus on validating these biomarkers in diverse populations and optimizing combination therapy protocols to minimize treatment burden while maximizing visual outcomes and systemic safety.